Advice to patients undergoing stem cell transplant: Content analysis of survivor peer support narratives. (May 2018) - Symes, Yael R; Barrington, Clare; Austin, Jane; Wu, Lisa M; Fisher, Edwin B; Rini, Christine
Hematopoietic stem cell transplant survivors often share advice with patients undergoing this difficult treatment. We content analyzed narratives written by 59 transplant survivors given the opportunity to share advice with patients. Analyses described categories of advice they shared and evaluated their perceptions of the helpfulness of advice they had received. We found nine advice categories and evidence for variation in their perceived helpfulness, especially for advice to "be your own advocate, " "have someone you can rely on, " and "think positive." Findings suggest the need to investigate how seemingly innocuous advice can be unhelpful and potentially distressing to some patients.